Hot corrosion behavior of thermal spray coatings on superalloy in coal-fired boiler environment - Kamal, S. (Cambridge University Press, 2015)
Coal is an attractive fuel owing to its low price linked to its worldwide availability but combustion of coal generates very corrosive media especially near the superheater tubes. The present investigation is an attempt to evaluate the hot corrosion behavior of detonation-gun sprayed coatings of Cr3C2-NiCr, NiCrAlY + 0.4 wt CeO2, and NiCoCrAlYTa on superfer 800H, exposed to low temperature super-heater zone of the coal-fired boiler. The specimens were hanged in the platen super-heater of coal-fired boiler where the gas temperature was around 900 °C ± 10 °C. Hot corrosion experiments were performed for 10 cycles, each cycle consisting of 100 h exposure followed by 1 h cooling at ambient temperature. All three coatings deposited on superfer 800H imparted better hot corrosion resistance than the bare uncoated one. The Cr3C2-NiCr coated superalloy performed better than the other two coatings in the given boiler environment. © Materials Research Society 2015.